Science and religion: evolutionism and creationism in education: a survey of teachers conceptions in 14 countries - Clément, Pierre (2008)
The renewed creationist movements are currently seen as a threat for science teaching in the world What is their impact on teachers' conceptions? We present here the results of a first large survey on this question, analysing teachers' conceptions in 14 countries (5 in Africa, 1 in Middle East and 9 in Europe). The total sample is composed of 5700 teachers (partly in-service, partly pre-service) of primary and secondary schools; 1846 of these teachers have biological training, 1787 have language training and 2077 have training to teach in primary school. We used a questionnaire including personal information and 15 questions on Evolution. The results show high significant differences between countries, religions, ageing, gender and level of instruction. This latter effect suggests the need for increasing the level of teachers’ training in order to overcome the current increasing creationist movements.